Characteristics of size-fractionated atmospheric metals and water-soluble metals in two typical episodes in Beijing. (October 2015) - Wang, Qingqing; Ma, Yongliang; Tan, Jihua; Zheng, Naijia; Duan, Jingchun; Sun, Yele; He, Kebin; Zhang, Yuanxun
Abstract: The abundance and behaviour of metals and water-soluble metals (V, Cr, Mn, Fe, Cu, Zn, As, Sr, Ag, Cd, Sn, Sb, Ba and Pb) in size-fractionated aerosols were investigated during two typical episodes in Beijing. Water-soluble inorganic ions (Na +, K +, Mg 2+, Ca 2+, N H 4 +, F −, Cl −, SO 4 2 − and NO 3 − ) were also measured. Atmospheric metals and water-soluble metals were both found at high levels; for PM2.5, average As, Cr, Cd, Cu, Mn and Pb concentrations were 14.8, 203.3, 2.5, 18.5, 42.6 and 135.3 ng/m 3, respectively, and their water-soluble components were 11.1, 1.7, 2.4, 14.5, 19.8 and 97.8 ng/m 3, respectively. Daily concentrations of atmospheric metals and water-soluble metals were generally in accordance with particle mass. The highest concentrations of metals and water-soluble metals were generally located in coarse mode and droplet mode, respectively. The lowest mass of metals and water-soluble metals was mostly in Aitken mode. The water solubility of all metals was low in Aitken and coarse modes, indicating that freshly emitted metals have low solubility. Metal water solubility generally increased with the decrease in particle size in the range of 0.26–10 μm. The water solubility of metals for PM10 was: 50% ≤ Cd, As, Sb, Pb; 26% < V, Mn, Cu, Zn and Sr ≤ 50%; others ≤20%. Most metals, water-soluble metals and their water solubility increased when polluted air mass came from the near west, near north-west, south-west and south-east of the mainland, and decreased when clean air mass came from the far north-west and far due south. The influence of dust-storms and clean days on water-soluble metals and size distribution was significant; however, the influence of rainfall was negligible. Aerosols with high concentrations of SO 4 2 −, K + and N H 4 + might indicate increased potential for human health effects because of their high correlation with water-soluble metals. Industrial emissions contribute substantially to water-soluble metal pollution as water-soluble metals show higher correlation with Cd, Sn, Sb and Pb that are mainly derived from industrial sources. Highlights: Metals and water-soluble metals were both at high level in Beijing. Water solubility of all metals was low in Aitken mode and coarse mode. Water-soluble metals had closer relationships with SO 4 2 −, K + and N H 4 + .